The relationship between social capital and knowledge sharing and their impact on improving the educational service quality: an analytical study of the views of a sample of academic staffs in the government universities in the Kurdistan Region of Iraq - حمد, حسيبة سليم; خال, سارا خالد (Journal of Economics and Administrative Sciences, 2019)
AbstractThis study aims to find the relationships between social capital (social network, social trust, shared goals) and knowledge sharing (knowledge Donating, knowledge collecting) as independent variables and their impact on improving the quality of educational services (academic staffs quality, Quality of teaching methods and study curriculums). This research is an important, because it attempts to identify the relationship between social capital and the knowledge sharing and their effect on improving the quality of educational service for universities. The study problem was determined in several questions related to the nature of the correlation relationship - the impact between the different independent variables (social capital and knowledge sharing) and the depended variable (educational service quality). SPSS program was used to analysis the collecting data. This research was applied on a sample of the government universities in the Kurdistan Region of Iraq. The results of the study showed the validity of hypotheses. In addition, a number of conclusions have been formulated, the most important of which is that there is a positive relationship between social capital and knowledge sharing. The study concluded with a number of recommendations which include a set of administrative mechanisms and practices that promote the building of social capital and the creation of a suitable environment for the development of the social capital.